2014
DOI: 10.3389/fpsyg.2014.01379
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in somatic awareness and interoceptive accuracy: a review of the literature and directions for future research

Abstract: This review examines cross-cultural differences in interoception and the role of culturally bound epistemologies, historical traditions, and contemplative practices to assess four aspects of culture and interoception: (1) the extent to which members from Western and non-Western cultural groups exhibit differential levels of interoceptive accuracy and somatic awareness; (2) the mechanistic origins that can explain these cultural differences, (3) culturally bound behavioral practices that have been empirically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 104 publications
3
75
0
Order By: Relevance
“…The expression of psychological states using bodily cues has been reported to reinforce physical symptoms. [56] Spirituality may however play adaptive role in influencing spiritbody dualism. Spiritual health was reflected in the belief that faith made all things possible, therefore if participants believed that they were healthy, this might facilitate a relinquishing of the sick role, leading to more active self-management with an internal locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of psychological states using bodily cues has been reported to reinforce physical symptoms. [56] Spirituality may however play adaptive role in influencing spiritbody dualism. Spiritual health was reflected in the belief that faith made all things possible, therefore if participants believed that they were healthy, this might facilitate a relinquishing of the sick role, leading to more active self-management with an internal locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of psychiatric classification 12,13 and social context may alter somatic symptom reporting 14 along with media coverage of health risks and iatrogenic factors 15 . As studies have mostly been cross-sectional and assessment methods have changed 16 , little is known about trends of somatic symptoms in the general population over time 10 . While numerous international studies and the growing awareness of mental health tend to create the impression that we are facing a surge of mental disorders, evidence is contradictory.…”
mentioning
confidence: 99%
“…Interoception is an important component of emotional regulation, and it is recognized that bodily state representations are also shaped by cultures (Ma‐Kellams, ). It has been shown that European Americans have better abilities in perceiving bodily sensations (i.e., interceptive accuracy) compared with West Africans or Asians (Chentsova‐Dutton & Dzokoto, ; Ma‐Kellams, Blascovich, & Mccall, ).…”
Section: Discussionmentioning
confidence: 99%